2018
DOI: 10.7717/peerj.4173
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Patagonian toothfish (Dissostichus eleginoides) in the Southeast Pacific and Southwest Atlantic Ocean

Abstract: Previous studies of population genetic structure in Dissostichus eleginoides have shown that oceanographic and geographic discontinuities drive in this species population differentiation. Studies have focused on the genetics of D. eleginoides in the Southern Ocean; however, there is little knowledge of their genetic variation along the South American continental shelf. In this study, we used a panel of six microsatellites to test whether D. eleginoides shows population genetic structuring in this region. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Numbers below bar correspond to locations; 1: Chile; 2: Falklands; 3: High Seas; 4: South Georgia; 5: SSI Second, RADSeq SNP genotyping confirmed nuclear differentiation and thus restricted bi-parental gene flow, between the samples on either side of the APF. This aligns with the differentiation reported by previous studies using microsatellites(Canales-Aguirre et al, 2018;Rogers et al, 2006) and confirms that the nonsignificant nuclear differentiation reported byShaw et al (2004) reflected insufficient statistical power rather than male biased gene flow per se. The higher statistical power conferred by RADSeq also permitted robust assignment of individuals to population of origin.Furthermore, outlier analysis identified individual SNPs exhibiting levels of divergence beyond neutral expectations in comparisons between samples across the APF, with no outliers identified when tests were restricted to comparisons among the Patagonian or South APF sites only: this pattern is compatible with divergent natural selection effects across the APF.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Numbers below bar correspond to locations; 1: Chile; 2: Falklands; 3: High Seas; 4: South Georgia; 5: SSI Second, RADSeq SNP genotyping confirmed nuclear differentiation and thus restricted bi-parental gene flow, between the samples on either side of the APF. This aligns with the differentiation reported by previous studies using microsatellites(Canales-Aguirre et al, 2018;Rogers et al, 2006) and confirms that the nonsignificant nuclear differentiation reported byShaw et al (2004) reflected insufficient statistical power rather than male biased gene flow per se. The higher statistical power conferred by RADSeq also permitted robust assignment of individuals to population of origin.Furthermore, outlier analysis identified individual SNPs exhibiting levels of divergence beyond neutral expectations in comparisons between samples across the APF, with no outliers identified when tests were restricted to comparisons among the Patagonian or South APF sites only: this pattern is compatible with divergent natural selection effects across the APF.…”
supporting
confidence: 90%
“…Genetic studies of toothfish have provided robust evidence of restricted genetic exchange between populations in Chilean and Patagonian waters, to the north of the APF, with populations south of the APF. Allozyme and microsatellite DNA markers have revealed significant nuclear differentiation between the Falkland Islands and populations south of the APF around Shag rocks and South Georgia (Appleyard et al ., 2004; Canales‐Aguirre et al ., 2018; Rogers et al ., 2006). Mitochondrial DNA restriction fragment length polymorphism (RFLP) analysis also reported a high level of mtDNA divergence between samples collected around the Falkland Islands and sites south of the APF (Shaw et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is widely accepted that the application of genetic knowledge is essential for the conservation and sustainable use of natural resources (Supple and Shapiro, 2018). However, and in contrast with the ecological, evolutionary, and economic importance of this species, the number of studies focused on the evaluation of genetic aspects of Patagonian toothfish are limited and isolated (Smith and McVeagh, 2000;Shaw et al, 2004;Rogers et al, 2006;Toomey et al, 2016;Canales-Aguirre et al, 2018). These studies have used either mitochondrial DNA or a very limited number of microsatellite (simple sequence repeat, SSR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…The most plausible hypotheses involve: (1) the mutation rate of the fragment, (2) the evolutionary rates hypothesis, or (3) the metabolic rate theory (e.g. 50 ). The mitochondrial control region is a high-mutation region organized in hypervariable regions flanking a central conserved region and is considered the most variant non-coding gene in fishes (e.g.…”
Section: Hyperdiversity In Diplodus Bellottiimentioning
confidence: 99%